Nanocomposite Platform Based on EDTA Modified Ppy/SWNTs for the Sensing of Pb(II) Ions by Electrochemical Method - Deshmukh, Megha A.; Bodkhe, Gajanan A.; Shirsat, Sumedh; Ramanavicius, Arunas; Shirsat, Mahendra D. (Frontiers in Chemistry, 2018)
NA